Fatal disseminated fusariosis during induction therapy for adult acute lymphoblastic leukemia in a patient with prior multiple myeloma - Sara Alberti; Gianluca Cavallaro; Alessandra Tebaldi; Paola Tebaldi; Maria Chiara Finazzi; Anna Grassi; Monica Galli; Laura Paris; Paola Stefanoni; Francesca Valsecchi; Alessandro Rambaldi; Federico Lussana (Mediterranean Journal of Hematology and Infectious Diseases, 2026)
Invasive fungal infections are a major cause of morbidity and mortality in patients with hematologic malignancies, particularly during prolonged neutropenia and intensive chemotherapy. In acute lymphoblastic leukemia (ALL), prophylaxis is challenging because mold-active azoles interact with vinca alkaloids and may increase hepatotoxicity with asparaginase, whereas provide incomplete coverage against Aspergillus spp. and rare molds such as Fusarium spp. We report a fatal case of proven cutaneous invasive fusariosis with radiologically presumed pulmonary dissemination during induction therapy for Philadelphia-negative B-cell precursor ALL (BCP-ALL) in a 58-year-old man with heavily pretreated multiple myeloma (MM).